Future of Parathyroid hormone and its analogues in dentistry - Dr. Richa Gupta, Dr. Swati Gupta, (International Journal of Scientific Research and Management (IJSRM), 2014)
Bone remodeling is a highly coordinatedphysiological process orchestrated by cross talksbetween various cells, pathways and signalingmolecules that are required to repair damagedbone and maintain mineral homeostasis. Boneregeneration is a complex physiological processthat aims to restore the original function andarchitecture of bone lost in cases of trauma,fracture, abnormal bone healing etc. To achievethis goal of bone regeneration, various bonesubstitutes like bone grafts, osteogenic stem cells,osteoconductive scaffolds, growth factors, barriermembranes have been used with mixed results.